Electrochemical immunosensor for ethinylestradiol using diazonium salt grafting onto silver nanoparticles-silica-graphene oxide hybrids - Cincotto, Fernando H. [UNESP]; Martinez-Garcia, Gonzalo; Yanez-Sedeno, Paloma; Canevari, Thiago. C.; Machado, S. A. S. [UNESP]; Pingarron, Jose M. (Elsevier B.V., 2016)
This work describes the preparation of an electrochemical immunosensor for ethinylestradiol (EE2) based on grafting of diazonium salt of 4-aminobenzoic acid onto a glassy carbon electrode modified with silver nanoparticles/SiO2/graphene oxide hybrid followed by covalent binding of anti-ethinylestradiol (anti-EE2) to activated carboxyl groups. A competitive immunoassay was developed for the determination of the hormone using peroxidase-labeled ethinylestradiol (HRP-EE2) and measurement of the amperometric response at -200 mV in the presence of hydroquinone (HQ) as redox mediator. The calibration curve for EE2 exhibited a linear range between 0.1 and 50 ng/mL (r(2)=0.996), with a detection limit of 65 pg/mL. Interference studies with other hormones related with EE2 revealed the practical specificity of the developed method for the analyte. A good reproducibility, with RSD=4.5% (n=10) was also observed. The operating stability of a single bioelectrode modified with anti-EE2 was maintained at least for 15 days when it was stored at 4 degrees C under humid conditions between measurements. The developed immunosensor was applied to the analysis of spiked urine with good results. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ethinylestradiol; EE2; Electrochemical immunosensor; Silver nanoparticles; Graphene oxide; Urine